2013
DOI: 10.5402/2013/916376
|View full text |Cite
|
Sign up to set email alerts
|

Serological and Molecular Evaluation of Leishmania infantum Infection in Stray Cats in a Nonendemic Area in Northern Italy

Abstract: Infection by Leishmania species is increasing worldwide. It was hypothesized recently that cats act as a secondary reservoir for Leishmania infection. The aim of the present study was to assess the prevalence of Leishmania infantum antibodies and DNA in blood samples collected in a sample of stray cats in metropolitan area of Milan in northern Italy, which is a nonendemic area for leishmaniasis. An indirect immunofluorescence antibody test for L. infantum showed that 59 of 233 cats (25.3%) were seroreactive, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 24 publications
8
38
2
2
Order By: Relevance
“…This is the second study to examine stray cats from the city of Milan for L. infantum infection. A previous study [22] reported a seropositivity of 6.4% for L. infantum at titers ≥1:80 (15 seropositive out of 233 cats tested) in stray colony cats, in contrast to the total negativity of blood samples analyzed by rPCR. Seropositivity for L. infantum was re-evaluated 4 years later in the present study in a similar population of stray cats in order to take advantage of the increased diagnostic sensitivity of newer PCR techniques for the identification of L. infantum in whole blood, lymph node aspirates, and oculoconjunctival samples.…”
Section: Discussionmentioning
confidence: 81%
“…This is the second study to examine stray cats from the city of Milan for L. infantum infection. A previous study [22] reported a seropositivity of 6.4% for L. infantum at titers ≥1:80 (15 seropositive out of 233 cats tested) in stray colony cats, in contrast to the total negativity of blood samples analyzed by rPCR. Seropositivity for L. infantum was re-evaluated 4 years later in the present study in a similar population of stray cats in order to take advantage of the increased diagnostic sensitivity of newer PCR techniques for the identification of L. infantum in whole blood, lymph node aspirates, and oculoconjunctival samples.…”
Section: Discussionmentioning
confidence: 81%
“…However, little is known about the clinical manifestations and immune response to the disease in these animals, which is well-established in dogs. Thus, various techniques have been used in the diagnosis of FL, such as serological, parasitological and molecular techniques [5,7,11,12,14,18,32,41].…”
Section: Discussionmentioning
confidence: 99%
“…Feline leishmaniosis (FL) cases have been reported in South America [5,[7][8][9][10][11], and in Europe [12][13][14][15][16][17][18] and Asia [19][20][21]. More properly in many cats the Leishmania infection is associated with an immunosuppressive condition due to feline leukemia virus and feline immunodeficiency virus, and for this reason there can be an overlap of clinical symptoms or the immunosuppression can promote the development of visceral forms of leishmaniosis [22].…”
Section: Introductionmentioning
confidence: 99%
“…Dirofilaria immitis, Ehrlichia canis, Hepatozoon canis) can influence parasite burden and progression of CanL (De Tommasi et al, 2013;Morgado et al, 2016;Tabar et al, 2013). In cats the association between retroviral, coronavirus, Toxoplasma or some vector-borne co-infections in cats antibody and/or PCR positive to L. infantum has been explored (Attipa et al, 2017;Ayllón et al, 2012;Pennisi et al, 2012Pennisi et al, , 2000Pennisi et al, , 1998Persichetti et al, 2016;Sherry et al, 2011;Sobrinho et al, 2012;Solano-Gallego et al, 2007;Spada et al, 2016Spada et al, , 2013Vita et al, 2005). A significant association between Feline Immunodeficiency Virus (FIV) and L. infantum positivity was found only in few cases (Pennisi et al, 1998;Sobrinho et al, 2012;Spada et al, 2013).…”
Section: Pathogenesis and Clinical Featuresmentioning
confidence: 99%